The genetic network underlying the evolution of pathogenicity in avian Escherichia coli - Palmieri, Nicola; Apostolakos, Ilias; Paudel, Surya; Hess, Michael (Frontiers in Veterinary Science, 2023)
Colibacillosis is a highly prevalent disease in poultry production linked to Escherichia coli strains that belong to the avian pathogenic E. coli (APEC) pathotype. While many virulence factors have been linked to APEC isolates, no single gene or set of genes has been found to be exclusively associated with the pathotype. Moreover, a comprehensive description of the biological processes linked to APEC pathogenicity is currently lacking. In this study, we compiled a dataset of 2015 high-quality avian E. coli genomes from pathogenic and commensal isolates, based on publications from 2000 to 2021. We then conducted a genome-wide association study (GWAS) and integrated candidate gene identification with available protein-protein interaction data to decipher the genetic network underlying the biological processes connected to APEC pathogenicity. We showed that convergent pathways related to nutrient uptake from host cells and defense from host immune system play a major role in APEC pathogenicity, but also identified novel candidate genes warranting further functional investigation. In addition, this dataset represents a comprehensive historical genomic collection of avian E. coli isolates and constitutes a valuable resource for their comparative genomics investigations.